Multiparametric monitoring of microbial faecal pollution reveals the dominance of human contamination along the whole Danube River. (1st November 2017) - Kirschner, A.K.T.; Reischer, G.H.; Jakwerth, S.; Savio, D.; Ixenmaier, S.; Toth, E.; Sommer, R.; Mach, R.L.; Linke, R.; Eiler, A.; Kolarevic, S.; Farnleitner, A.H.
Abstract: The microbial faecal pollution of rivers has wide-ranging impacts on a variety of human activities that rely on appropriate river water quality. Thus, detailed knowledge of the extent and origin of microbial faecal pollution is crucial for watershed management activities to maintain safe water use. In this study, the microbial faecal pollution levels were monitored by standard faecal indicator bacteria (SFIB) along a 2580 km stretch of the Danube, the world's most international river, as well as the Danube's most important tributaries. To track the origin of faecal pollution, host-associated Bacteroidetes genetic faecal marker qPCR assays for different host groups were applied in concert with SFIB. The spatial resolution analysis was followed by a time resolution analysis of faecal pollution patterns over 1 year at three selected sites. In this way, a comprehensive faecal pollution map of the total length of the Danube was created, combining substantiated information on both the extent and origin of microbial faecal pollution. Within the environmental data matrix for the river, microbial faecal pollution constituted an independent component and did not cluster with any other measured environmental parameters. Generally, midstream samples representatively depicted the microbial pollution levels at the respective river sites. However, at a few, somewhat unexpected sites, high pollution levels occurred in the lateral zones of the river while the midstream zone had good water quality. Human faecal pollution was demonstrated as the primary pollution source along the whole river, while animal faecal pollution was of minor importance. This study demonstrates that the application of host-associated genetic microbial source tracking markers in concert with the traditional concept of microbial faecal pollution monitoring based on SFIB significantly enhances the knowledge of the extent and origin of microbial faecal pollution patterns in large rivers. It constitutes a powerful tool to guide target-oriented water quality management in large river basins. Graphical abstract: Longitudinal development of E. coli and Enterococci concentrations along the increasing discharge (grey shaded area) of the Danube in the midstream, at the left (upper line) and the right river-side (lower line) and in the tributaries sampled during JDS 2013. Not-sampled tribtaries are also indiacted on the x-axes. Symbol size varies according to log-transformed E. coli and Enterococci concentrations. Colours depict the faecal pollution levels: blue - little, green - moderate, yellow - crtitical, orange - strong and red excessive pollution. Grey-shaded triangles indicate discharge contributions from the main tributaries. Highlights: Faecal pollution patterns along the whole Danube river are shown. Combination of standard parameters and microbial source tracking markers used. Dominance of anthropogenic pollution along the whole Danube River. Midstream samples generally depict microbial faecal pollution levels. High pollution levels of the lateral zones at specific, partly unexpected sites.